Improving Children's Language Development Aspects through Role Playing at Mutiara Hati Kindergarten - Zainiah, Veni; Susanto, Rezi; Fitri, Yulia Rahmi (CV. Strata Persada Academia, 2025)
This classroom action research (CAR) aimed to enhance children's language development through role-playing at Mutiara Hati Kindergarten in Solok Selatan. Language skills are crucial for early childhood communication, cognition, and socialization, yet many schools prioritize literacy and numeracy over holistic development. The study involved 10 children and one teacher across two cycles, using observation (based on Indonesian Ministry of Education benchmarks) and documentation. Results showed significant improvement: while Cycle I saw most children at